TERT genetic polymorphism rs2736100 is associated with an aggressive manifestation of papillary thyroid carcinoma - Nie, Xilin; Shang, Jinbiao; Wang, Wendong (Frontiers in Surgery, 2023)
Objectives TERT rs2736100 genetic polymorphism is commonly found in human malignancies, indicating its key role in cancer cell transformation. The aim of this study is to investigate the effects of the functional TERT rs2736100 genetic polymorphism on the outcomes of papillary thyroid carcinoma (PTC) patients. Materials and methods We performed a retrospective study on the relationship between rs2736100 and clinicopathological outcomes of PTC in 500 patients (378 females and 122 males) aged 43.8 ± 11.4 years (range 15–74 years) with a median follow-up of 60 months (range, 1–455 months). Results TERT rs2736100 genetic polymorphism (TG/GG vs. TT) was significantly associated with several high-risk clinicopathological features such as tumor spread, extrathyroidal extension, central/lateral lymph node metastases, and Stage T III or IV disease. However, in Kaplan–Meier survival analyses, the rs2736100 mutation was unrelated to overall disease-free survival with a log-rank value of p > 0.05. In Cox-regression analyses, the overall survival rate of recurrence/neo-metastasis was related to a larger tumor size, younger age, and tumor spread but unrelated to the rs2736100 mutation. Conclusions and significance TERT rs2736100 genetic polymorphism mutation is more likely to manifest with aggressive clinicopathological characteristics but cannot worsen prognosis in PTC.